Wolf's Isotopic Response after Herpes Zoster Infection: A Study of 24 New Cases and Literature Review - Tao Wang; Min Zhang; Ying Zhang; Yu Zhang; Shiyu Zhang; Tao Qu; Yuehua Liu; Hongzhong Jin (Medical Journals Sweden, 2019)
Wolf's isotopic response refers to the occurrence of a new skin disease at the exact site of an unrelated skin disease that had previously healed. Various cutaneous lesions have been described after herpes zoster. This study included 24 patients with Wolf's isotopic response after herpes zoster infection, which presented as manifestations ranging from inflammatory disease to carcinoma. Histopathological examinations in 12 patients and immunohistochemical analyses in 10 patients allowed exploration of secondary microscopic changes in the lesions. CD4+/CD8+ T-cell ratios were normal and infiltrating cells included mast cells, eosinophils, and tumour cells. Our study has described additional patients with confirmed Wolf's isotopic response following herpes zoster infection; moreover, it has extended the spectrum of Wolf's isotopic response to include impetigo. We suggest Wolf's isotopic response classification categories for herpes zoster-associated Wolf's isotopic response. Additionally, clinicians should consider the possibilities of different diseases in Wolf's isotopic response, especially malignancies.